2005
DOI: 10.1073/pnas.0504610102
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Drosophila DJ-1 leads to impairments of oxidative stress response and phosphatidylinositol 3-kinase/Akt signaling

Abstract: Parkinson's disease ͉ PI3K͞PTEN͞Akt signaling ͉ reactive oxygen species P arkinson's disease (PD) is the most common movement disorder and the second most common neurodegenerative disease. The movement abnormality in PD arises from deficiency of brain dopamine (DA) contents and the degeneration of dopaminergic neurons in the substantia nigra. The most common forms of PD are sporadic with no known cause. Nevertheless, postmortem studies have identified common features associated with sporadic PD, including defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
292
2
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 333 publications
(314 citation statements)
references
References 43 publications
18
292
2
2
Order By: Relevance
“…Although the precise cellular distribution of the PD protein DJ-1 is unsettled, it has been shown to protect against neuronal apoptosis associated with oxidative stress, possibly by functioning as a redoxsensitive co-transcriptional activator [1,65]. DJ-1-deficient mice are hypersensitive to MPTP and oxidative stress [10], and inhibition of DJ-1A function in Drosophila by RNA interference (RNAi) results in a number of defects, including hypersensitivity to oxidative stress, degeneration of dopaminergic neurons and impaired phosphatidylinositol 3-kinase (PI3K)/Akt signaling [66]. Interestingly, the same authors also observed impaired PI3K/Akt signaling in parkin RNAi transgenic flies, hinting at a common pathway in the pathogenesis of these PD genes [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise cellular distribution of the PD protein DJ-1 is unsettled, it has been shown to protect against neuronal apoptosis associated with oxidative stress, possibly by functioning as a redoxsensitive co-transcriptional activator [1,65]. DJ-1-deficient mice are hypersensitive to MPTP and oxidative stress [10], and inhibition of DJ-1A function in Drosophila by RNA interference (RNAi) results in a number of defects, including hypersensitivity to oxidative stress, degeneration of dopaminergic neurons and impaired phosphatidylinositol 3-kinase (PI3K)/Akt signaling [66]. Interestingly, the same authors also observed impaired PI3K/Akt signaling in parkin RNAi transgenic flies, hinting at a common pathway in the pathogenesis of these PD genes [66].…”
Section: Discussionmentioning
confidence: 99%
“…DJ-1-deficient mice are hypersensitive to MPTP and oxidative stress [10], and inhibition of DJ-1A function in Drosophila by RNA interference (RNAi) results in a number of defects, including hypersensitivity to oxidative stress, degeneration of dopaminergic neurons and impaired phosphatidylinositol 3-kinase (PI3K)/Akt signaling [66]. Interestingly, the same authors also observed impaired PI3K/Akt signaling in parkin RNAi transgenic flies, hinting at a common pathway in the pathogenesis of these PD genes [66].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, this hypersensitivity to oxidative stress is also seen in the neurons of dj-1-deficient mice (Kim et al, 2005b). In both organisms, the increased susceptibility to oxidative stress can be rescued by activation of the PI3 0 K pathway (Kim et al, 2005b;Meulener et al, 2005;Yang et al, 2005). Other work has implicated DJ-1 as a sensor of reactive oxygen species and as a molecular chaperone (Shendelman et al, 2004), and DJ-1 may be able to influence the protein stability or oxidative state of elements of the PI3 0 K pathway.…”
Section: Links Between Pten Dj-1 and Pdmentioning
confidence: 92%
“…Firstly, during tumorigenesis, the degradation of p27 kip1 can be driven by either PTEN or UCH-L1 (Caballero et al, 2002;Viglietto et al, 2002). Secondly, deletions of the Parkin gene in Drosophila result in PKB/Akt activation (Yang et al, 2005). Thirdly, PINK1, which encodes a kinase downregulated in the absence of PTEN, has been identified as the sixth locus (PARK6) associated with familial PD (West et al, 2005).…”
Section: Links Between Pten Dj-1 and Pdmentioning
confidence: 99%
See 1 more Smart Citation